2011
DOI: 10.1007/978-1-4419-5638-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Pro-survival and Anti-inflammatory Phenotype by Modulation of Acetylation in Models of Hemorrhagic and Septic Shock

Abstract: Shock, regardless of etiology, is characterized by decreased tissue perfusion resulting in cell death, organ dysfunction, and poor survival. Current therapies largely focus on restoring tissue perfusion through resuscitation but have failed to address the specific cellular dysfunction caused by shock. Acetylation is rapidly emerging as a key mechanism that regulates the expression of numerous genes (epigenetic modulation through activation of nuclear histone proteins), as well as functions of multiple cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 160 publications
(204 reference statements)
0
26
0
Order By: Relevance
“…This study supports our previous results, which showed that VPA administration protects neurons against hypoxiainduced apoptotic cell death 28 and activates innate cell survival pathways. 29 Another mechanism of cell survival lies in the autogenic strengthening and remodeling of cell structural components in response to injury. We found significant overexpression of NEFL and SIX4, two genes that play an important role in the regeneration, differentiation, and maturation of neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study supports our previous results, which showed that VPA administration protects neurons against hypoxiainduced apoptotic cell death 28 and activates innate cell survival pathways. 29 Another mechanism of cell survival lies in the autogenic strengthening and remodeling of cell structural components in response to injury. We found significant overexpression of NEFL and SIX4, two genes that play an important role in the regeneration, differentiation, and maturation of neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have proven that HDACi have anti-inflammatory and cell-protective effects in traumatic brain injury, stroke, and ischemia reperfusioninduced oxidative damage. [13][14][15] Trichostatin A (TSA), one of the HDAC inhibitors, selectively inhibits the class I and II mammalian histone deacetylase (HDAC) families of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Even the patients that survive the acute episode of blood loss often develop multiple organ dysfunction syndrome (MODS) due to tissue hypoxia and systemic inflammation (2, 3). Tissue hypoxia with resultant anaerobic metabolism has long been considered a leading etiology of post-shock MODS (4).…”
Section: Introductionmentioning
confidence: 99%